Polyphenols and Cannabidiol Modulate Transcriptional Regulation of Th1/Th2 Inflammatory Genes Related to Canine Atopic Dermatitis - Massimini, Marcella; Dalle Vedove, Elena; Bachetti, Benedetta; Di Pierro, Francesco; Ribecco, Cataldo; D'Addario, Claudio; Pucci, Mariangela (Frontiers in Veterinary Science, 2021)
Canine atopic dermatitis (AD) is a multifactorial allergic disease associated with immune and abnormal skin barrier dysfunction and is one of the primary causes of pruritus. Using a novel in vitro model of AD, we here evaluated the altered transcriptional regulation of AD canine key genes and how a nutraceutical mixture, containing a flavonoid, stilbene and cannabinoid, already well-known for their applications within dermatology disease, is able to revert these alterations. The nutraceutical mixture induced in inflamed cells a significant down-regulation (p<0.05) of the expression of ccl2, ccl17 and tslp in keratinocytes and of ccl2, ccl17 and il31ra mRNA levels in monocytes. Consistently with the gene expression alterations for tslp mRNA in keratinocytes as well as for ccl2, ccl17 and il31ra gene expression, a significant increase (p<0.05) in DNA methylation at specific CpG sites of gene regulatory regions was observed. These results lay the foundation for the use of these natural bioactives in veterinary medicine and provide a model for a deeper understanding of their mechanisms of action, with potential translation to human research.